Unlocking Agile's missed potential - Webber, Robert (Wiley-IEEE Computer Society Pr, 2022)
"This book makes the case that the potential of Agile development in software product management was lost because feature-based Waterfall planning forces engineering into so-called "hybrid" approaches that don't support basic tenets of Agile development. A new Agile planning process based on value flow optimization can unleash Agile, taking companies into a new era of business agility and financial predictability. The author introduces a practical way to unify Agile practices across the product development life cycle, from ideation through deployment. This holistic perspective facilitates collaboration and teamwork among product management, engineering, and project management to finally realize the promises of Agile development."--